1993
DOI: 10.1093/infdis/167.3.584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Age on Cytotoxic T Lymphocyte Memory as well as Serum and Local Antibody Responses Elicited by Inactivated Influenza Virus Vaccine

Abstract: Healthy seropositive adults aged < 40 (n = 15), 40-64 (n = 15), and > or = 65 (n = 17) years were parenterally immunized with trivalent subvirion influenza virus vaccine, and their cellular and humoral immune responses were compared. Vaccination resulted in a significant enhancement of class I human leukocyte antigen-restricted influenza A cross-reactive cytotoxic T lymphocyte (CTL) memory. Elderly subjects had significantly lower baseline and peak postvaccination mean percentages of specific lysis of influenz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
93
3

Year Published

1994
1994
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(100 citation statements)
references
References 42 publications
4
93
3
Order By: Relevance
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 60 eligible articles published between 1987 and 2006 describing inactivated seasonal influenza vaccine immunogenicity studies conducted in the United States, Canada, Europe, Israel, and Russia 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 . We included 129 independent study arms of which 119 reported data on response to A/H1N1, 109 on influenza B, and 108 on A/H3N2 vaccine strains (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…The reduced protection is believed to be due to poor stimulation of cellular immunity (Powers et al, 1993;McElhaney et al, 2006) and risk for influenza illness in vaccinated older adults is associated with low levels of granzyme (GrB), a key cytolytic mediator of the CTL response to influenza (McElhaney et al, 2001;Schmidt et al, 2004). This current study focused on age-related changes in the virus-specific memory CTL (CD8+) response to influenza that may explain the increased risk of influenza illness in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…These include T-cell proliferation in response to stimulation through T cell receptor and co-stimulators (Engwerda et al, 1994;Lerner et al, 1988;Song et al, 1993), production and response to growth promoting cytokines (Ernst et al, 1993;Nagelkerken et al, 1991;Saxena et al, 1988) and generation of cytotoxic T-cells (Hirano and Nordin, 1976;Powers and Belshe, 1993;Mbawuike et al, 1997). We have previously characterized mitogen induced cytotoxic spleen cells from young and old mice and reported differences in their cytolytic activities (Saxena et al, 1981(Saxena et al, , 1988a.…”
Section: Introductionmentioning
confidence: 99%